2015
DOI: 10.2147/ndt.s85380
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the prevalence and incidence of Parkinson’s disease in the People’s Republic of China

Abstract: BackgroundParkinson’s disease (PD) is a common neurodegenerative disease, and obtaining accurate epidemiological data for this disease is very important for policy-making in public health. The purpose of this study was to determine the prevalence and incidence of PD in the People’s Republic of China and explore possible future research directions.MethodsWe systematically retrieved studies of the prevalence and incidence of PD in the People’s Republic of China, Taiwan, and Hong Kong, and standardized the data a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 19 publications
1
39
1
Order By: Relevance
“…The record‐based studies showed a lower prevalence rate (35.8–68.3/100,000) . A recent meta‐analysis of 15 Asian studies on Chinese (10 China, two Hong Kong, three Taiwan) showed a prevalence rate of 16–440.3/100,000 (age standardized to 2000 WHO population) . The older studies from China had a lower prevalence rate, however, it was higher in a study from the elderly resident homes in Hong Kong during the same period .…”
Section: Pd Prevalencementioning
confidence: 96%
See 3 more Smart Citations
“…The record‐based studies showed a lower prevalence rate (35.8–68.3/100,000) . A recent meta‐analysis of 15 Asian studies on Chinese (10 China, two Hong Kong, three Taiwan) showed a prevalence rate of 16–440.3/100,000 (age standardized to 2000 WHO population) . The older studies from China had a lower prevalence rate, however, it was higher in a study from the elderly resident homes in Hong Kong during the same period .…”
Section: Pd Prevalencementioning
confidence: 96%
“…In a meta‐analysis, the prevalence among the age groups 70–79 years was less in Asians compared to the Western population . These differences could be related to the smaller sample size, lower response rate, misdiagnosis, and different survival times …”
Section: Pd Prevalencementioning
confidence: 97%
See 2 more Smart Citations
“…With a prevalence ranging from 35.8 per 100,000 to 12,500 per 100,000 and annual incidence estimates ranging from 1.5 per 100,000 to 346 per 100,000 in different countries [1,2,3], PD is becoming a major age-related problem of health [4,5]. Meta-analysis of the worldwide data indicates a rising prevalence of PD with age (41 per 100,000 at 40–49 years; 107 at 50–59 years; 173 at 55–64 years; 428 at 60–69 years; 425 at 65–74 years; 1087 at 70–79 years; and 1903 per 100,000 at over age 80), also reflecting a characteristic distribution by geographic location (a prevalence of 1601 per 100,000 in patients from North America, Europe and Australia, and a prevalence of 646 per 100,000 in Asian patients [6].…”
Section: Introductionmentioning
confidence: 99%